2015
DOI: 10.1016/j.bbrc.2015.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid transport protein-2 inhibitor Grassofermata/CB5 protects cells against lipid accumulation and toxicity

Abstract: The inhibition of the fatty acid uptake into non-adipose tissues provides an attractive target for prevention of lipotoxicity leading to obesity-associated non-alcoholic fatty liver disease and type 2 diabetes. Fatty acid transport proteins (FATPs) are bifunctional proteins involved in the uptake and activation of fatty acids by esterification with coenzyme A. Here we characterize Grassofermata/CB5, previously identified as a fatty acid uptake inhibitor directed against HsFATP2. The compound was effective in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
(42 reference statements)
2
17
0
Order By: Relevance
“…As predicted, treatment of cells with this compound does not alter medium chain fatty acid transport. Consistent with in vitro studies, Grassofermata, like Lipofermata when delivered orally, prevents intestinal absorption of 13 C labeled oleate 117 . Pharmacokinetic data show this inhibitor is detectible in the blood within 30 minutes of dosing and for up to 6 hours indicating it is absorbed as well 117 .…”
Section: Grassofermatasupporting
confidence: 76%
See 1 more Smart Citation
“…As predicted, treatment of cells with this compound does not alter medium chain fatty acid transport. Consistent with in vitro studies, Grassofermata, like Lipofermata when delivered orally, prevents intestinal absorption of 13 C labeled oleate 117 . Pharmacokinetic data show this inhibitor is detectible in the blood within 30 minutes of dosing and for up to 6 hours indicating it is absorbed as well 117 .…”
Section: Grassofermatasupporting
confidence: 76%
“…Like Lipofermata, Grassofermata is inhibits the transport of fluorescent fatty acid-analog C 1 -BODIPY-C 12 in various cell lines that are models for small intestine, liver, pancreatic islets, muscles and human adipocytes 102 . Inhibition by Grassofermata is specific for long and very long chain fatty acid transport and is protective effects against palmitic acid induced lipoapoptosis 39, 116, 117 . As predicted, treatment of cells with this compound does not alter medium chain fatty acid transport.…”
Section: Grassofermatamentioning
confidence: 99%
“…2B). FATP2 is highly expressed in the small intestine and our previous results showed that control mice treated with the FATP2-specific inhibitor, Lipofermata, were compromised in their ability to absorb dietary fatty acids (13) and thus, we expected Fatp2 -/mice would result in comparable outcomes. Male mice were fasted and following the intraperitoneal injection of tyloxapol to inhibit lipoprotein lipase-dependent systemic fatty acid uptake, they were gavaged with 500 mg/kg uniformly 13 C-labeled oleate (C18:1) in flaxseed oil.…”
Section: Resultsmentioning
confidence: 91%
“…Emerging evidence suggests increased expression of FATP2 is linked to non-alcoholic fatty liver disease, renal disease and some cancers (2,(11)(12)(13). Under conditions of lipid overload, increased expression of FATP2 in the liver leads to increased fat accumulation, inflammation and organellar dysfunction (10,14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation